Repurposing of dextromethorphan as an adjunct therapy in patients with major depressive disorder: a randomised, group sequential adaptive design, controlled clinical trial protocol - Shampa Maji; Rituparna Maiti; Anand Srinivasan; Debadatta Mohapatra; Monalisa Jena (BMJ Open, 2024)
Background Therapeutic latency, lack of efficacy and adverse drug reactions are the major concerns in current antidepressant therapies. To overcome these treatment hurdles, add-on therapy to conventional antidepressant medications may lead to better therapeutic outcomes. The present randomised controlled trial has been planned to evaluate the efficacy and safety of add-on dextromethorphan to selective serotonin reuptake inhibitors (SSRIs) in major depressive disorder (MDD).Methods and analysis A randomised, double-blind, add-on, placebo-controlled, group sequential design clinical trial will be conducted on patients with MDD who will be randomly assigned to the control and the test group in a 1:1 ratio. Patients in the test group will get dextromethorphan 30 mg once daily, whereas patients in the control group will receive a placebo once daily as an add-on to ongoing SSRI treatment for 8 weeks. All patients will be evaluated for the primary outcome (change in the Montgomery-Åsberg Depression Rating Scale score) and secondary outcomes (treatment response rate, remission rate, Clinical Global Impression, serum brain-derived neurotrophic factor, serum dextromethorphan and treatment-emergent adverse events) over the period of 8 weeks. Intention-to-treat analysis will be done for all parameters using suitable statistical tools.Ethics and dissemination This study was approved by the Institutional Ethics Committee of All India Institute of Medical Sciences, Bhubaneswar, India, and the study conformed to the provisions of the Declaration of Helsinki and ICMR’s ethical guidelines for biomedical research on human subjects (2017). Written informed consent will be obtained from the participants before recruitment. The results of this study will be published in peer-reviewed publications.Trial registration number NCT05181527.